Emulsan quantitation by Nile red quenching fluorescence assay - Castro, Guillermo Raúl (2005)
A Nile red fluorescent technique to quantify 20– 200 μg ml⁻¹ of emulsan was developed. Nile red dissolved in DMSO showed an adsorption peak at 552 nm, and emission peak at 636 nm, with molar extinction coefficient of 19,600 cm⁻¹ M⁻¹. Nile red fluorescence in DMSO was proportionally quenched by emulsan and the quenching was time-dependent. The assay was used to follow the production of emulsan by cultures of Acinetobacter venetianus RAG⁻¹.